Insights on the Biomarker Identification for Chronic Gastritis with TCM Damp Phlegm Pattern [Response to Letter] - You Z; Zhang J; Xu Y; Lu J; Zhang R; Zhu Z; Wang Y; Hao Y (Journal of Inflammation Research)
Zhiyuan You,1 Jialin Zhang,1 Yifeng Xu,1 Junhong Lu,1 Renling Zhang,2 Zhujing Zhu,3 Yiqin Wang,1 Yiming Hao1 1Shanghai Key Laboratory of Health Identification and Assessment/Laboratory of TCM Four Diagnostic Information, Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People’s Republic of China; 2Gastroenterology, Longhua Hospital Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People’s Republic of China; 3Rheumatology, Longhua Hospital Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People’s Republic of ChinaCorrespondence: Yiming Hao, Email hymjj888@163.com